Crafting educational programs in modern business schools: A transformative shift in values and culture - Ressin, Marat (Journal of Interdisciplinary Studies in Education, 2026)
The study is dedicated to determining the association of responsible management in education on the transformation of education in contemporary business schools. The research examines the association of responsible management on the survival of companies established by business school graduates, based on a survey of 140 graduates from colleges and universities in the United States and Canada, whose companies have been operational for over three years. Using ANOVA to compare respondents’ assessments across socio-demographic and educational groups (gender, background, work experience, and education quality), it was found that the evaluations of the influence of responsible management vary statistically significantly between these groups. These results suggest potential implications for business education, while remaining limited to associative interpretation.